Penerapan ANOVA Dengan Respon Data Count Pada Kasus Perkecambahan Serbuk Sari Jagung - Rusdiana, Riza Yuli; Fariroh, Indri (Universitas Madako Tolitoli, 2025)
In agriculture, ANOVA is often used to determine the effect of different treatments (categories) on the response (continuous). Research in the field found many cases that aim to evaluate the difference in treatment where the response in the form of data count. In this study, ANOVA will conduct a one-way ANOVA analysis study on the response in the form of count data by applying one-way ANOVA standard, transformation and poisson approach. The data used are six datasets to observe the number of corn pollen sprouts. The results showed the statistical decisions of the six datasets gave consistent decisions on each method. The performance of the standard one-way ANOVA method and poisson approach provides the same conclusions to each dataset. Based on AIC and BIC criteria, poisson approach is recommended in response data count especially count data that contains zero value. This method does not require assumptions of normality and homoscedasticity to be met.